Education And Training To Improve The Performance Of Save And Loan Cooperative Employees In Bandung District West Java Province - Rosmayati, Siti; Kuswarno, Engkus; Mudrikah, Achmad; Iriantara, Yosal (International Journal of Educational Research & Social Sciences, 2021)
The function and role of cooperatives is to build and develop the economic potential and capabilitiesof members in particular and the community in general to improve their economic and social welfare,to actively participate in efforts to improve the quality of human and community life in accordancewith Law Number 25 of 1992 concerning cooperatives. In producing cooperative members who areprosperous and competitive with other cooperatives, they must comply with the National ProfessionalCertificate Agency (BNSP), as regulated in education, on the standards of educators and educationpersonnel where the so-called trainer states that the trainer must have academic qualifications as aninformation agent, physically fit and spiritual, and have the ability to create healthy and qualitycooperatives. As a trainer, the curriculum in education and training is set for those who are moreexperienced at least 2 years of service in the cooperative where they work. Employees who providetraining in the organization's internal environment will contribute to producing competent employeesand members who will replace when the savings and loan cooperative employees' term of officeexpires. In order to improve the competence of savings and loan cooperative employees, one of them isby developing capabilities, through education and training. This study aims to describe education andtraining as an increase in the competence of savings and loan cooperative employees througheducation and training carried out through several stages, namely: 1) Analysis of education andtraining needs of savings and loan cooperative employees, 2) Design and planning of education andtraining for savings cooperative employees, 3) Development of education and training curriculum forsavings and loan cooperative employees, 4) Implementation of education and training for savings andloan cooperative employees, 5) Evaluation of education and training for savings and loan cooperativeemployees, 6) barriers and education and training support capacity of savings and loan cooperativeemployees. To achieve this objective, a qualitative approach was conducted using the case studymethod at KPRI and Primkoppabri, Cicalengka District. Data were collected using in-depthinterviews, observation and documentation studies. The research data was checked for correctness,reliability through a triangulation process. The results showed that the process of implementingeducation and training for savings and loan cooperative employees in cooperatives was not supportedby a complete analysis of education and training needs. In addition, the two cooperatives studied onlycarried out evaluations during training, had not carried out post-training evaluations andcomprehensive program evaluations so they could not monitor change actions. The weak point thatappears in the implementation of education and training for savings and loan cooperative employeesis that there is no separate unit, so the lack of experience in managing education and training isabbreviated as education and training. The involvement and commitment of all parties, especially themanagement or management will be the key to the success of the training education program. the twocooperatives studied only conducted evaluations during training, had not carried out post-trainingevaluations and comprehensive program evaluations so they could not monitor change actions. Theweak point that appears in the implementation of education and training for savings and loancooperative employees is that there is no separate unit, so the lack of experience in managingeducation and training is abbreviated as education and training. The involvement and commitment ofall parties, especially the management or management will be the key to the success of the trainingeducation program. the two cooperatives studied only conducted evaluations during training, had notcarried out post-training evaluations and comprehensive program evaluations so they could notmonitor change actions. The weak point that appears in the implementation of education and trainingfor savings and loan cooperative employees is that there is no separate unit, so the lack of experiencein managing education and training is abbreviated as education and training. The involvement andcommitment of all parties, especially the management or management will be the key to the success ofthe training education program. The weak point that appears in the implementation of education andtraining for savings and loan cooperative employees is that there is no separate unit, so the lack ofexperience in managing education and training is abbreviated as education and training. Theinvolvement and commitment of all parties, especially the management or management will be the keyto the success of the training education program. The weak point that appears in the implementationof education and training for savings and loan cooperative employees is that there is no separate unit,so the lack of experience in managing education and training is abbreviated as education andtraining. The involvement and commitment of all parties, especially the management or managementwill be the key to the success of the training education program.